A Contrastive Study on Indonesian and English Question Words - I Dewa Putu Wijana Putu Wijana (Faculty of Language and Literature, University of Surakarta, 2023)
Interrogative sentences constitute one of the most important modes of sentences in any world language. By this type of sentence, the language speakers can get information regarding everything they do not know, something they hesitate, or anything that the hearer wants to agree with. As such, this mode of sentence should be mastered by all language learners. However, like any other mode of sentences, interrogative sentences are also differently structured across languages, bringing serious difficulties for all second language learners. Moreover, languages do not belong to the same family group, like Indonesian, which belongs to the Austronesian family group, and English, which belongs to the Indo-German family group. Concerning this matter, this research paper will briefly describe the differences in the use of Indonesian question words apa, siapa, berapa, di mana, bagaimana,and kapan and its English contrast with what, who, how many/much, where and when. By contrasting Indonesian interrogative sentences containing apa, siapa, berapa, di mana, bagaimana, and kapan, and how they are expressed in English, it is found that not all these Indonesian question words can be directly and translated into what, who, how many/much, where and when. These differences will hopefully enhanche awareness of all language learners about the individualities or peculiarities owned by any language to ease their learning processes.